تدرج المسؤولية الجزائية للأحداث الجانحين - مكائيل تميم (Latakia University Journal - Economic and Legal Sciences Series, 2017)
في الحقيقة, إن مرحلة الحداثة هي من أهم المراحل التي يمر بها الإنسان حيث أنه من خلال هذه المرحلة تتحدد مقوماته الشخصية و ميوله الذاتية و تتكون ثقافته و تبرز علاقاته الاجتماعية على ساحة حياته. فطفل اليوم هو رجل الغد. و إذا ما استحوذنا عليه بالحماية و الحنان و الأمان و الرعاية و تنشئته الحرة الفطرية أو المكتسبة و وفرنا له سبيل العيش الآمن من مآكل و ملبس و حالة صحية خالية من الأمراض العضوية و النفسية استطعنا أن نبني رجل جديد ذو ميول اجتماعية غير عدائية ضد الأخر أو ضد المجتمع وابتعدنا به عن طريق الانحراف. إنّ قانون الأحداث السوري انطلق في توقيف الحدث من مبدأ مصلحة الحدث، ولم يضع شروطاً وضوابط خاصّة تحّد من سلطة القاضي في تقدير هذه المصلحة، وأجاز التوقيف بالنسبة لجميع الأحداث، وأياً كانت الجريمة المرتكبة. وخوفاً من احتمال وقوع أيّ تعسّف من قبل القاضي، وانطلاقاً من المنطق القانوني، يتوجّب وضع شروط خاصّة بتوقيف الحدث وتحديد نطاقه وقصره على الأحداث الذين أتموّا الخامسة عشرة، في حال ارتكابهم جناية واضحة المعالم وتكفي دلائلها الأولية لإدانة الحدث. إذ إنّه من غير المعقول اتخاذ مثل هذا الإجراء الزجري والخطير بحق باقي الأحداث، في حين أنّه لا تطبّق عليهم أيّة عقوبة سالبة للحرية، وإنّما تُطبّق عليهم التدابير الإصلاحية المنصوص عنها في المادّة الرابعة من قانون الأحداث الجانحين. و لابد من البحث عن تدابير بديلة ذات طابع تربوي وإصلاحي، يستعاض بها عن الاحتجاز والتوقيف. In fact, the modern stage is one of the most important stages throughout the human as it is during this phase is determined by effervescence personal inclinations and self-composed and culture and highlight the social relations on the yard of his life. Child today is a man of tomorrow. And if they hauled him protection and affection, and security and care and free upbringing innate or acquired, and we have provided to him for safe living, including food and clothing and health condition-free organic diseases and psychiatric we were able to build a new man with a social tendencies is hostile against the other or against society and we stepped away from him through the deviation. The Syrian Juveniles Act launched in the event of the arrest of the principle of the benefit of the event, and did not set conditions and special controls limit the power of the judge to appreciate this interest, and authorized the detention for all events, regardless of the crime committed. Fearing the possibility of the occurrence of any abuse by the judge, on the basis of legal logic, should put special conditions arrest event and determine the scope and restricted to juveniles who have completed fifteen, when committed a felony and clear-cut enough of primary significance to condemn the event. As it is unreasonable to make such a restraining order against the dangerous and the rest of the events action, while it does not apply to them any penalty involving freedom, but apply to them reform measures provided for in Article IV of the Juvenile Delinquents Act. And must seek out an educational character of alternative measures and reform, would replace the detention and arrest.